Optimization of the biomass production of Kluyveromyces marxianus in whey. (FAVE Sección Ciencias Veterinarias, 2021)
Whey is a by-product of cheese making and represents a danger of environmental contamination when discarded without prior treatment. However, due to its high content of lactose, vitamins and proteins, whey should not be considered a waste, but rather a raw material for obtaining value-added products. Among the alternatives for its use, biomass production stands out through fermentation with Kluyveromyces marxianus. Therefore, this work determines the best operating conditions for biomass production, minimizing residual lactose. To this end, a Doehlert Experimental Matrix Design was used to optimize the effects of aeration and nitrogen source concentration on the growth of K. marxianus by a minimum number of experiments. The results obtained allow maximizing the biomass production, the consumption of lactose and protein by K. marxianus, thus achieving a more effective treatment of whey prior to its discard.
Keywords: whey, biomass, Kluyveromyces marxianus